2018
DOI: 10.2147/ijn.s172162
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical, docking, and cellular studies on the effects of cerium oxide nanoparticles on blood components: in vitro

Abstract: IntroductionThe application of nanoparticles (NPs) in medicine and biology has received great interest due to their novel features. However, their adverse effects on the biological system are not well understood.Materials and methodsThis study aims to evaluate the effect of cerium oxide nanoparticles (CNPs) on conformational changes of human hemoglobin (HHb) and lymphocytes by different spectroscopic (intrinsic and synchronous fluorescence spectroscopy and far and near circular dichroism [CD] spectroscopy), do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…This result suggests that, in our experimental conditions, the maximum concentration of NC recommended for safe application is 50 μg/mL. A recent study demonstrates that, although NC did not significantly perturb the native conformation of hemoglobin, they can stimulate some adverse effects on circulating lymphocytes at concentrations higher 50 μg/mL that may limit their biomedical application . Moreover, the fibrinogen levels were within normal limits even if lower levels were observed at higher NC concentrations.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…This result suggests that, in our experimental conditions, the maximum concentration of NC recommended for safe application is 50 μg/mL. A recent study demonstrates that, although NC did not significantly perturb the native conformation of hemoglobin, they can stimulate some adverse effects on circulating lymphocytes at concentrations higher 50 μg/mL that may limit their biomedical application . Moreover, the fibrinogen levels were within normal limits even if lower levels were observed at higher NC concentrations.…”
Section: Discussionsupporting
confidence: 48%
“…A recent study demonstrates that, although NC did not significantly perturb the native conformation of hemoglobin, they can stimulate some adverse effects on circulating lymphocytes at concentrations higher 50 μg/mL that may limit their biomedical application. 35 Moreover, the fibrinogen levels were within normal limits even if lower levels were observed at higher NC concentrations. This slight decrease, that did not influence blood coagulation, as showed by APTT and PT tests, could be due to processes of absorption and/or binding of fibrinogen on NC surface, as observed in other studies investigating the affinity of plasma proteins for different NP surfaces.…”
Section: Discussionmentioning
confidence: 84%
“…It was depicted that CeO 2 NPs show an average diameter of around 30 nm with a vibration peak at 738 cm −1 22. Indeed, potential transport of therapeutic agents like NPs into the human brain is one of the most demanding tasks in anti-amyloid drug development owing to the blood-brain barrier (BBB).…”
Section: Resultsmentioning
confidence: 99%
“…α-Syn, Thioflavin T (ThT), 8-anilinonaphthalene-1-sulfonic acid (ANS), Congo red, Dulbecco’s Modified Eagle Medium/Nutrient Mixture F-12 (DMEM: F12), fetal bovine serum (FBS), L-glutamine, penicillin, streptomycin, and MTT were purchased from Sigma Co. (St. Louis, MO, USA). CeO 2 NPs, purity: 99.97%, APS: 10–30 nm, SSA: 30–50 m 2 /g, bulk density: ~0.8–1.1 g/cm 3 , and true density: 7.132 g/cm 3 were purchased from US Research Nanomaterials, Inc. (Houston, USA) and well characterized by different approaches in our previous paper 22…”
Section: Methodsmentioning
confidence: 99%
“…However, several reports suggested that the uptake of nanoceria could induce oxidative stress and DNA damage, apoptosis, dephosphorylation of various substrates, aberrant cell signaling, and alterations in the transcriptional and posttranslational levels. 3,[30][31][32] Biomedical Relevance of Nanoceria Kailashiya, Dash…”
Section: Toxicity and Adverse Effectsmentioning
confidence: 99%